ASSESSMENT OF KNOWLEDGE AND AWARENESS ABOUT LEPROSY AMONG MEDICAL COLLEGE STUDENTS IN MEWAT REGION OF HARYANA - Garima, Gini; Sharma, Abhishek; sharma, Sudhanshu; singh, Nikita; Vohra, Prakriti; Sharma, Nidhi; Singh, Sangeeta (International Journal of Clinical and Biomedical Research, 2018)
Introduction -Leprosy is a chronic infectious disease which still remains a serious public health problem due to its ability to cause disability. The prevention of leprosy ultimately lies in the early diagnosis and treatment of the individuals having leprosy. Changing leprosy scenario has led to requirement of leprosy education. However the knowledge of medical college students on leprosy remains unknown. Aim: To assess the post-sensitization knowledge and awareness of medical students after state leprosy sensitization program. Materials and methods: A questionnaire based, cross sectional study was conducted among 107 medical students of different years starting from 2nd year and onwards in the month of July 2017 after state leprosy sensitization program. Results: Among the medical students 70 (75%) were male students and 37(25%) were female students coming from different years of their admission in medical college .Regarding the basic knowledge of leprosy 100 % of 3nd year and final year students were having knowledge about the cause of leprosy and 100% of final year and 3rd year medical students know about other name of Leprosy (Hansen,s disease) respectively.100% of final year, 3rd year and 2nd year medical students had knowledge about multidrug therapy (MDT) in in-depth knowledge of leprosy respectively. Regarding the virulence of bacilli 87%, 60% and 63% of final, 3rd and 2nd year medical students had apt knowledge respectively. Conclusion-These observations suggest that the basic and in-depth knowledge of medical students about cause, types, prevention and treatment etc. of leprosy shows increasing trend owing to the part of their curriculum. However there is still a need to organize sensitization programs at regular intervals to impart basic and in-depth knowledge to new medical students, as well as to update the knowledge of those who already had such sensitization programs. Keywords: Awareness; Knowledge; Leprosy; Sensitization.